Developing of Bachelor Housewives Entrepreneurship - Elianti, Anisa (Prosiding Seminar; 2019: 2019 International Conference of Interdisciplinary Sciences, 2019)
Housewives with bachelor degree being a controversial position. Some of people believe being housewives are nurturing families and building up the society but others are conceived that being housewives is useless, not productive and unimportant. As bachelor housewives, actually they already have a good background study and science because they already educated well. But now days, we often see the housewives being a jobless and not productive even if they are still in the very productive age. It caused by the job vacancy which available for the married women is very few. This phenomenon makes the writer concern in developing bachelor housewives entrepreneurship. The entrepreneurship itselfalso need tools to be success. Character and social media usage may be the tools in developing entrepreneurship. The writer discuss each tool related to the previous article that already discussed about character and social media usage in entrepreneurship to see the role of each factor especially in developing bachelor housewife entrepreneurship.